Ecological assessment of an algaecidal naphthoquinone derivate for the mitigation of Stephanodiscus within a mesocosm. (October 2017) - Joo, Jae-Hyoung; Kuang, Zhen; Wang, Pengbin; Park, Bum Soo; Patidar, Shailesh Kumar; Han, Myung-Soo
Abstract: The novel eco-friendly algaecidal naphthoquinone derivate was used to control harmful algal bloom causing species Stephanodiscus and, its effect was assessed on other undesired and non-targeted microbial communities. We conducted a mesocosm experiment to investigate the effects of this novel algaecide on native microbial communities rearing in water collected from Nakdonggang River. Upon treatment of the mesocosm with the naphthoquinone derivate the concentration of Chl- a decreased from 20.4 μg L −1 to 9.5 μg L −1 after 2 days. The turbidity has also shown decrement (exhibited 15.5 NTU on the 7th day). The concentrations of DOC and phosphate in the treatment were slightly higher than those in the control due to the decomposition of dead Stephanodiscus, whereas the DO and pH in the treated condition were slightly lower than those in the control; which was due to increment of organic acids and higher degradation activity. Results showed that bacterial abundance were not significantly different but community composition were slightly different as revealed by NGS (Next generation sequencing). The variation in HNF (Heterotrophic nanoflagellates) revealed that the bacterial community composition changed following the change in bacterial abundance. During the treatment, the abundance of Stephanodiscus was significantly reduced by more than 80% after 6 days, and the abundance of ciliates and the dominant species, Halteria grandinella, had shown marked decline. The abundance of zooplankton sharply decreased to 5 ind. L −1 on the 8th day but increased again by the end of the study period. The Shannon-Wiener diversity index of phytoplankton, ciliates and zooplankton in the treated mesocosm increased significantly after 4, 7 and 8 days, respectively. The marked changes in the ecosystem structure were observed in treatment compare to control. However, the beneficial microalgal populations were not affected which indicated possibility of restoration of treated ecosystem and regain of healthy community structure after certain period. Graphical abstract: Highlights: This novel NQ derivative can be an effective, selective and safe algaecidal substance. NQ derivative did not causes the secondary pollution or disturb the freshwater ecosystem. The diversity of the microbial communities significantly increased after adding NQ derivative.